Parents' Views of Family-Centered Care at a Pediatric Intensive Care Unit—A Qualitative Study - Terp, Karina; Weis, Janne; Lundqvist, Pia (Frontiers in Pediatrics, 2021)
Abstract Purpose To describe parents’ views of family-centered care at a pediatric intensive care unit. Design and methods A qualitative descriptive study with a deductive and inductive approach was conducted based on the principles of family-centered care. Inclusion criteria were parents of children cared for at a pediatric intensive care unit for at least 48 hours. Parents of children who died during the hospital stay were excluded. The sample consisted of spontaneous responses from 70 parents to five open questions in the EMpowerment of PArents in THe Intensive Care questionnaire, which was completed at discharge. The spontaneous responses were analyzed using thematic analysis. Results The results illuminated an uneven partnership. Partnership was particularly evident regarding parents’ experiences of being treated with empathy and respect. It also seemed prominent in situations when the professional team provided support for the child, parents, and family. Based on the parents’ statements there was potential for development of the family-centered care approach in aspects such as decision-making concerning care and treatment, and in improving person-centered communication that could capture parents’ experiences and needs in the highly technological pediatric intensive care unit environment. Conclusions Although in general parents were satisfied with the care, areas for improvement were identified such as participation in decision-making about care and treatment as well as person-centered communication. The results can contribute to future quality improvement interventions focusing family centered care at pediatric intensive care units.